IMPLEMENTATION OF THE MADRASAH WORKING GROUP PROGRAM IN UTILIZING INFORMATION TECHNOLOGY AT MADRASAH ALIYAH NEGERI 1 PRABUMULIH - Megawati Megawati; Zainal Berlian; Nazarudin Nazarudin; Ade Akhmad Saputra (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2021)
The purpose of this study was to analyze how the Implementation of the Madrasah Working Group Program in Utilizing Information Technology to Support Great Madrasas, Dignified Madrasas at Prabumulih State Aliyah 1 Madrasah. This research is a qualitative research. In data collection, researchers used several collection techniques, namely: (1) in-depth interviews, (2) observation, (3) documentation study. The data analysis technique uses the analytical method using the Miles and Huberman Model which consists of three stages, namely: data reduction, data display, and drawing conclusions or verification. The results of this research are the Implementation of the Madrasah Working Group Program in Utilizing Information Technology to Support Great Madrasahs, Dignified Madrasas at Prabumulih Aliyah Negeri 1 Madrasah priority program, namely; First, vocation, namely improving infrastructure and student apprenticeships in the industrial world. Second, mastery of science, technology, engineering, and mathematics (STEM). Third, increasing Information-Technology literacy. Fourth, mastery of foreign languages, especially Arabic and English. And Fourth, to make it happen, socialization, program preparation, program implementation and evaluation are needed.